Method for preparing sintering process raw slurry by using high-iron red mud
By conducting component analysis of high-speed rail red mud and proportional mixing of raw slurry, the complexity of high-speed rail red mud in the sintered alumina production is solved, efficient alumina production is achieved, production costs and impurities are reduced, and impurities are increased. Recovery rate and kiln operation stability.
Patent Information
- Application Number
- CN202411207261.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
AI Technical Summary
In the production of sintered alumina, the complex components and interactions of high-speed iron red mud make it difficult to control, resulting in difficulty in recycling and utilization. The cost of using refined iron ore or high-speed iron bauxite is high, and the existing technology cannot be effective Reduce impurity content and production costs in alumina products.
By conducting component analysis of high-speed rail red mud, combining the proportion of bauxite, limestone, coal, silicon slag and alkali liquid, adjusting the iron-aluminum ratio and calcium ratio of raw material slurry, and adjusting it with high-speed rail red mud and limestone to ensure the growth rate. The aluminum-silicon ratio of the slurry, the weight ratio of the silicon slag and the weight ratio of the high-speed iron red mud to bauxite are within the optimal range, and a high-quality sintering raw material slurry is prepared.
The effective reuse of high-speed rail red mud has been achieved, the ore and alkali consumption in alumina production has been reduced, the recovery rate of alumina and sodium oxide has been improved, the production cost has been reduced, and the net dissolution rate of clinker and kiln has been increased. Operation stability.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of producing alumina by sintering method, and specifically relates to a method for preparing raw material slurry of sintering method by using high-iron red mud. Background Art
[0002] In the production process of alumina by sintering, the iron-aluminum ratio of raw slurry directly affects the sintering temperature and clinker quality. During the batching process of raw slurry, the iron-aluminum ratio of raw slurry needs to be kept within a certain range. The Fe2O3 content of domestic monohydrate bauxite is mostly in the range of 2%-7%. The iron-aluminum ratio of ore alone can only reach 0.055-0.065, which is a certain gap from the normal raw slurry iron-aluminum ratio requirement of 0.075-0.081. Therefore, when preparing sintering raw slurry, in order to stabilize the raw slurry formula, in addition to using domestic monohydrate bauxite, a certain amount of refined iron ore or high-iron bauxite needs to be added to adjust the iron-aluminum ratio of raw slurry. The cost of using refined iron ore or high-iron bauxite to prepare raw slurry is relatively high.
[0003] High-iron red mud is a waste product produced by the Bayer process of alumina production. The Fe2O3 content reaches 40%-50%, and it contains a large amount of aluminum oxide and sodium oxide. In addition, its alkalinity is also high. Direct discharge will cause resource waste and environmental pollution. However, due to the complex composition of high-iron red mud and the interaction between the components, its physical and chemical properties are difficult to control, so its recycling is relatively difficult. Although current researchers have conducted a lot of research on the recycling of high-iron red mud, there are still few technologies that can truly achieve industrialization and scale. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing sintering raw material slurry using high-iron red mud, and the present invention specifically includes the following contents:
[0005] A method for preparing sintering raw material slurry with high-iron red mud, comprising the following steps:
[0006] S1, drying the high iron red mud and conducting component analysis;
[0007] S2, mixing bauxite, limestone, coal, high-iron red mud, silicon slag and alkali solution in a mass ratio of 1:(04-0.8):(0.1-0.2):(0.15-0.2):(0.2-0.6):(0.60-0.65) and grinding to prepare a raw slurry, and then analyzing the aluminum-silicon ratio and the weight proportion of silicon slag in the raw slurry;
[0008] S3, according to the aluminum-silicon ratio of the raw slurry, the weight proportion of silicon slag, the weight ratio of high-iron red mud to bauxite, and the analysis results of the high-iron red mud composition, high-iron red mud and limestone are added to the raw slurry to adjust the iron-aluminum ratio and calcium ratio of the raw slurry respectively, and finally the sintering method raw slurry is obtained. The specific adjustment ratio is:
[0009] When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0003; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.003-0.007;
[0010] When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0002; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.001-0.005.
[0011] Preferably, the specific adjustment ratio in step S2 is:
[0012] When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00018-0.00022; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.004-0.006;
[0013] When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00012-0.00018; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.002-0.004.
[0014] Preferably, the specific adjustment ratio in step S2 is:
[0015] When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00019-0.00021; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.0045-0.006;
[0016] When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00014-0.00016; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.0025-0.0040.
[0017] Preferably, the alkali solution is a sodium carbonate solution with a concentration of 220-240 g / L.
[0018] The net dissolution rate of the clinker obtained after dehydration and calcination of the sintering raw material slurry prepared by the method of the present invention is greater than 90%.
[0019] Beneficial effects of the present invention:
[0020] In the prior art, when using iron ore and the like to prepare raw material slurry, it is only necessary to control the aluminum-silicon ratio, iron-aluminum ratio, calcium ratio, alkali ratio, etc. within a certain range to meet the production requirements. However, when using high-iron red mud to prepare raw material slurry, since high-iron red mud contains a large amount of other impurities in addition to iron, only controlling the aluminum-silicon ratio, iron-aluminum ratio, calcium ratio, alkali ratio, etc. within a certain range cannot meet the production needs, which will lead to problems such as high impurity content in the final alumina product and poor alumina quality. Therefore, although high-iron red mud can theoretically be used to prepare sintering raw material slurry, there are great difficulties in actual application, so no producer currently uses it to prepare raw material slurry.
[0021] The method described in the present invention first analyzes the composition of the high-iron red mud after drying; then mixes bauxite, limestone, raw coal, silicon slag and alkali solution to prepare raw slurry, and then analyzes the aluminum-silicon ratio and the weight proportion of silicon slag in the raw slurry; finally, according to the aluminum-silicon ratio of the raw slurry, the weight proportion of silicon slag, the weight ratio of high-iron red mud to bauxite, and the results of the high-iron red mud component analysis, high-iron red mud and limestone are added to the raw slurry to adjust the iron-aluminum ratio and calcium ratio of the raw slurry. The present invention creatively combines the aluminum-silicon ratio, silicon slag weight ratio, high iron red mud and bauxite weight ratio, iron-aluminum ratio and calcium ratio of the raw slurry, and judges the optimal iron-aluminum ratio and calcium ratio by detecting the aluminum-silicon ratio, silicon slag weight ratio and high iron red mud and bauxite weight ratio in the raw slurry, and then calculates the amount of high iron red mud to be added according to the component analysis result of high iron red mud, and adjusts the iron-aluminum ratio and calcium ratio of the raw slurry to the optimal range by adding high iron red mud and limestone. The net dissolution rate of the clinker obtained after dehydration and calcination of the raw slurry according to the method disclosed in the present invention is greater than 90, and the clinker kiln operates stably. In addition, the method can also improve the recovery rate of aluminum oxide and sodium oxide in high iron red mud, reduce the ore consumption and alkali consumption in production, and realize the waste recycling of high iron red mud and reduce pollution while reducing the production cost of aluminum oxide. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with specific embodiments. The embodiments shown below do not limit the invention content described in the claims. In addition, the entire contents of the structures represented by the following embodiments are not limited to those necessary as solutions to the invention described in the claims.
[0023] A method for preparing sintering raw material slurry with high-iron red mud, comprising the following steps:
[0024] S1, drying the high iron red mud and conducting component analysis;
[0025] S2, mixing bauxite, limestone, coal, high iron red mud, silicon slag and alkali solution in a mass ratio of 1:(04-0.8):(0.1-0.2):(0.15-0.2):(0.2-0.6):(0.60-0.65) and grinding, and then analyzing the aluminum-silicon ratio and the weight proportion of silicon slag in the raw slurry; the alkali solution is a sodium carbonate solution with a concentration of 220-240 g / L;
[0026] S3, according to the aluminum-silicon ratio of the raw slurry, the weight proportion of silicon slag, the weight ratio of high-iron red mud to bauxite, and the analysis results of the high-iron red mud composition, high-iron red mud and limestone are added to the raw slurry to adjust the iron-aluminum ratio and calcium ratio of the raw slurry respectively, and finally the sintering method raw slurry is obtained. The specific adjustment ratio is:
[0027] When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0003 (preferably 0.00019-0.00021, and most preferably 0.0002); for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.003-0.007 (preferably 0.0045-0.0060, and most preferably 0.005);
[0028] When the aluminum-silicon ratio in the raw material slurry is 3.5≤<4.2, in the raw material slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0002 (preferably 0.00014-0.00016, and most preferably 0.00015); for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.001-0.005 (preferably 0.0025-0.0040, and most preferably 0.0003).
[0029] The net dissolution rate of the clinker obtained after dehydration and calcination of the sintering raw material slurry prepared by the method of the present invention is greater than 90%.
[0030] The method of the present invention first analyzes the components of the high-iron red mud after drying; then mixes bauxite, limestone, raw coal, silicon slag and alkali solution to prepare raw slurry, and then analyzes the aluminum-silicon ratio and the weight proportion of silicon slag in the raw slurry; finally, according to the aluminum-silicon ratio of the raw slurry, the weight proportion of silicon slag, the weight ratio of high-iron red mud to bauxite, and the results of the high-iron red mud component analysis, high-iron red mud and limestone are added to the raw slurry to adjust the iron-aluminum ratio and calcium ratio of the raw slurry. The present invention creatively combines the aluminum-silicon ratio, silicon slag weight ratio, high iron red mud and bauxite weight ratio, iron-aluminum ratio and calcium ratio of the raw slurry, and judges the optimal iron-aluminum ratio and calcium ratio by detecting the aluminum-silicon ratio, silicon slag weight ratio and high iron red mud and bauxite weight ratio in the raw slurry, and then calculates the amount of high iron red mud to be added according to the component analysis result of high iron red mud, and adjusts the iron-aluminum ratio and calcium ratio of the raw slurry to the optimal range by adding high iron red mud and limestone. The net dissolution rate of the clinker obtained after dehydration and calcination of the raw slurry according to the method disclosed in the present invention is greater than 90, and the clinker kiln operates stably. In addition, the method can also improve the recovery rate of aluminum oxide and sodium oxide in high iron red mud, reduce the ore consumption and alkali consumption in production, and realize the waste recycling of high iron red mud and reduce pollution while reducing the production cost of aluminum oxide.
[0031] Example 1
[0032] After bauxite, limestone, coal (i.e., raw coal), and high-iron red mud are measured by a belt scale, mixed in proportion, and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1:0.4:0.1:0.15:0.2:0.60 (mass ratio, the same below), and the alkali solution is a sodium carbonate solution with a concentration of 220g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively regulated by adding high-iron red mud and limestone, and the regulation method is:
[0033] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0003 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0034] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.005 for every 1% increase in the weight ratio of high-iron red mud / ore (i.e., bauxite).
[0035] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.3%-97.1%, and the net dissolution rate is 90.3%-91.1%.
[0036] It should be noted that each embodiment of the present invention was subjected to multiple experiments and tests under the same conditions. Due to many factors such as operating errors, the dissolution rate obtained by the test will fluctuate within a small range.
[0037] Example 2
[0038] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.8: 0.2: 0.2: 0.6: 0.65, and the alkali solution is a sodium carbonate solution with a concentration of 240 g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0039] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0002 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0040] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.005 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0041] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.8%-97.6%, and the net dissolution rate is 90.6%-92.3%.
[0042] Example 3
[0043] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.6: 0.15: 0.18: 0.4: 0.62, and the alkali solution is a sodium carbonate solution with a concentration of 230 g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0044] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0001 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0045] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.005 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0046] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.2%-96.7%, and the net dissolution rate is 90.2%-90.8%.
[0047] Example 4
[0048] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.5: 0.12: 0.18: 0.5: 0.63, and the alkali solution is a sodium carbonate solution with a concentration of 228 g / L. The raw slurry is tested for components multiple times, and the results show that the aluminum-silicon ratio in this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the control method is:
[0049] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0002 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0050] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.003 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0051] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.4%-97.1%, and the net dissolution rate is 90.3%-91.6%.
[0052] Example 5
[0053] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.7: 0.18: 0.16: 0.3: 0.645, and the alkali solution is a sodium carbonate solution with a concentration of 232g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0054] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0002 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0055] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.004 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0056] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.6%-97.4%, and the net dissolution rate is 90.5%-91.9%.
[0057] Example 6
[0058] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.8: 0.2: 0.15: 0.2: 0.60, and the alkali solution is a sodium carbonate solution with a concentration of 235 g / L. The raw slurry is tested for components multiple times, and the results show that the aluminum-silicon ratio in this embodiment fluctuates between 2.8-3.5. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the control method is:
[0059] When the raw slurry has an aluminum-silicon ratio of 2.8≤<3.5, the iron-aluminum ratio of the raw slurry increases by 0.0002 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0060] When the aluminum-silicon ratio of the raw slurry is 2.8≤<3.5, the calcium ratio of the raw slurry increases by 0.006 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0061] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.4%-96.8%, and the net dissolution rate is 90.2%-91.7%.
[0062] Example 7
[0063] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1:0.8:0.2:0.2:0.6:0.65, and the alkali solution is a sodium carbonate solution with a concentration of 227g / L. The raw slurry is tested for components several times, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 3.5-4.2. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the control method is:
[0064] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the iron-aluminum ratio of the raw slurry increases by 0.0002 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0065] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the calcium ratio of the raw slurry increases by 0.003 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0066] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.6%-97.7%, and the net dissolution rate is 90.6%-92.1%.
[0067] Example 8
[0068] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.6: 0.15: 0.18: 0.4: 0.62, and the alkali solution is a sodium carbonate solution with a concentration of 230 g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 3.5-4.2. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0069] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the iron-aluminum ratio of the raw slurry increases by 0.00015 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0070] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the calcium ratio of the raw slurry increases by 0.003 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0071] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.8%-97.6%, and the net dissolution rate is 91.2%-92.7%.
[0072] Example 9
[0073] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.5: 0.16: 0.17: 0.5: 0.63, and the alkali solution is a sodium carbonate solution with a concentration of 230 g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 3.5-4.2. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0074] When the raw slurry has an aluminum-silicon ratio of 3.5 ≤ <4.2, the iron-aluminum ratio of the raw slurry increases by 0.0001 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0075] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the calcium ratio of the raw slurry increases by 0.004 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0076] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.2%-96.7%, and the net dissolution rate is 90.5%-91.3%.
[0077] Example 10
[0078] After bauxite, limestone, coal, and high-iron red mud are measured by a belt scale, they are mixed in proportion and sent to a ball mill together with silicon slag and alkali solution for grinding to obtain a raw slurry, wherein the ratio of bauxite: limestone: coal: high-iron red mud: silicon slag: alkali solution is controlled to be 1: 0.8: 0.2: 0.15: 0.3: 0.64, and the alkali solution is a sodium carbonate solution with a concentration of 230 g / L. The raw slurry is subjected to multiple component tests, and the results show that the aluminum-silicon ratio of this embodiment fluctuates between 3.5-4.2. According to the test results, the aluminum-silicon ratio and calcium ratio in the raw slurry are respectively adjusted by adding high-iron red mud and limestone, and the adjustment method is:
[0079] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the iron-aluminum ratio of the raw slurry increases by 0.00015 for every 1% increase in the weight proportion of silicon slag in the raw slurry;
[0080] When the aluminum-silicon ratio of the raw slurry is 3.5≤<4.2, the calcium ratio of the raw slurry increases by 0.004 for every 1% increase in the weight ratio of high-iron red mud / ore.
[0081] Finally, a raw material slurry meeting the requirements is obtained, and the raw material slurry is dehydrated and calcined to obtain clinker. After production tests, the standard dissolution rate of the clinker obtained in this embodiment is 96.8%-97.4%, and the net dissolution rate is 90.6%-92.1%.
[0082] In summary, the net dissolution rate of the clinker obtained by dehydrating and calcining the sintering raw material slurry prepared by the method of the present invention is greater than 90%.
[0083] Comparative Example 1
[0084] The difference between this comparative example and Example 1 is that the aluminum-silicon ratio of the raw slurry is simply controlled to be 2.8≤<3.5, and the iron-aluminum ratio and calcium ratio are not adjusted according to the weight proportion of silicon slag in the raw slurry.
[0085] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 76.3%-77.1%, and the net dissolution rate is 70.1%-72.4%.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is only that:
[0088] For every 1% increase in the weight proportion of silicon slag in the raw slurry, the iron-aluminum ratio of the raw slurry increases by 0.0005; for every 1% increase in the weight ratio of high-iron red mud / ore, the calcium ratio of the raw slurry increases by 0.009.
[0089] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 81.3%-83.1%, and the net dissolution rate is 76.1%-77.0%.
[0090] Comparative Example 3
[0091] The difference between this comparative example and Example 1 is only that:
[0092] For every 1% increase in the weight proportion of silicon slag in the raw slurry, the iron-aluminum ratio of the raw slurry increases by 0.00005; for every 1% increase in the weight ratio of high-iron red mud / ore, the calcium ratio of the raw slurry increases by 0.001.
[0093] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 77.3%-78.2%, and the net dissolution rate is 71.5%-72.4%.
[0094] Comparative Example 4
[0095] The difference between this comparative example and Example 7 is that the aluminum-silicon ratio of the raw slurry is simply controlled to be 3.5≤<4.2, and the iron-aluminum ratio and calcium ratio are not adjusted according to the weight proportion of silicon slag in the raw slurry.
[0096] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 76.6%-77.3%, and the net dissolution rate is 70.2%-72.3%.
[0097] Comparative Example 5
[0098] The difference between this comparative example and Example 7 is only that:
[0099] For every 1% increase in the weight proportion of silicon slag in the raw slurry, the iron-aluminum ratio of the raw slurry increases by 0.0003; for every 1% increase in the weight ratio of high-iron red mud / ore, the calcium ratio of the raw slurry increases by 0.008.
[0100] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 80.3%-82.5%, and the net dissolution rate is 75.81%-76.4%.
[0101] Comparative Example 6
[0102] The difference between this comparative example and Example 7 is only that:
[0103] For every 1% increase in the weight proportion of silicon slag in the raw slurry, the iron-aluminum ratio of the raw slurry increases by 0.00005; for every 1% increase in the weight ratio of high-iron red mud / ore, the calcium ratio of the raw slurry increases by 0.0005.
[0104] The raw material slurry finally obtained is dehydrated and calcined to obtain clinker. After production test, the standard dissolution rate of the clinker obtained in this comparative example is 77.1%-78.5%, and the net dissolution rate is 71.6%-72.7%.
[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing sintering raw material slurry using high iron red mud, characterized in that: The following steps are involved: S1, drying the high iron red mud and conducting component analysis; S2, bauxite, limestone, coal, high iron red mud, silicon slag, alkali solution 1:(04-0.8):(0.1-0.2):(0.15-0.2):(0.2-0.6):(0.60-0.65) in mass ratio and then ground to prepare raw slurry, and then analyze the aluminum-silicon ratio and silicon slag weight proportion of the raw slurry; S3, according to the aluminum-silicon ratio of the raw slurry, the weight proportion of silicon slag, the weight ratio of high-iron red mud to bauxite, and the analysis results of the high-iron red mud composition, high-iron red mud and limestone are added to the raw slurry to adjust the iron-aluminum ratio and calcium ratio of the raw slurry respectively, and finally the sintering method raw slurry is obtained. The specific adjustment ratio is: When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0003; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.003-0.007; When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.0001-0.0002; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.001-0.
005.
2. The method for preparing sintering raw material slurry with high iron red mud according to claim 1, characterized in that: The specific adjustment ratio in step S2 is: When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00018-0.00022; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.004-0.006; When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00012-0.00018; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.002-0.
004.
3. The method for preparing sintering raw slurry with high iron red mud according to claim 2, characterized in that: The specific adjustment ratio in step S2 is: When the aluminum-silicon ratio in the raw slurry is 2.8≤<3.5, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00019-0.00021; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.0045-0.006; When the aluminum-silicon ratio in the raw slurry is 3.5≤<4.2, in the raw slurry: for every 1% increase in the weight proportion of silicon slag, the iron-aluminum ratio is adjusted to increase by 0.00014-0.00016; for every 1% increase in the weight ratio of high-iron red mud to bauxite, the calcium ratio is adjusted to increase by 0.0025-0.0040.
4. The method for preparing sintering raw material slurry with high iron red mud according to claim 1, characterized in that: The alkali solution is a sodium carbonate solution with a concentration of 220-240 g / L.
5. The method for preparing sintering raw slurry with high iron red mud according to any one of claims 1 to 4, characterized in that: The net dissolution rate of the clinker obtained after the sintering method raw material slurry is dehydrated and calcined is greater than 90%.